Emerging hantaviruses in Central Argentina: First case of Hantavirus Pulmonary Syndrome caused by Alto Paraguay virus, and a novel orthohantavirus in Scapteromys aquaticus rodent - Bellomo, Carla; Alonso, Daniel Oscar; Ricardo, Tamara; Coelho, Rocío; Kehl, Sebastián; Periolo, Natalia; Azogaray, Viviana; Casas, Natalia; Ottonelli, Mariano; Bergero, Laura Cristina; Cudós, María Carolina; Previtali, María Andrea; et al. (PLOS Neglected Tropical Diseases, 2021)
Author summary The term Hantavirus groups viruses that can cause human diseases and also viruses considered non-pathogenic. An increasing number of rodents, bats, shrew and moles have been identified as hantavirus reservoirs. Hantavirus pulmonary syndrome (HPS) is a severe disease caused by some of these viruses transmitted by rodent species. HPS is considered an emerging disease due to the enormous diversity of reservoirs that have been identified, which implicate new geographical areas affected and novel potential transmission routes. Their high fatality rates make it a serious public health concern. In the COVID-19 pandemic context, we described an HPS case in Central Argentina but outside the known endemic area. The infecting hantavirus characterized was Alto Paraguay virus, considered non-pathogenic to date. In order to identify the reservoir implicated, a study was carried out in available rodent samples from a nearby area. Although we were not able to find its reservoir, unexpectedly, a new hantavirus was identified: Leyes orthohantavirus. Additionally, a new reservoir was also identified, Scapteromys aquaticus. Our findings implicate an epidemiological warning regarding these new hantaviruses circulating in Central Argentina. There are no vaccines or specific treatments for HPS, therefore prevention actions are a key to reduce the impact of this disease.